Asymmetric discouragement in asymmetric contests - Christoph March; Marco Sahm (Bamberg University, Bamberg Economic Research Group (BERG), 2016)
We provide new experimental evidence which suggests an asymmetric discouragement effect in lottery contests with heterogeneous abilities. Compared to a symmetric contest, subjects invest less effort when facing a stronger opponent, but they invest the same when facing a weaker opponent. Our results can be explained by a simple model of disappointment aversion.
Keywords: C72; C92; D72; 330; Asymmetric Contest; Discouragement Effect; Disappointment Aversion; Laboratory Experiment